Stakeholder approach to selecting enterprise-bank interaction strategies - Hutsaliuk, Oleksii M.; Yaroshevska, Oksana V.; Shmatko, Nataliia M.; Kulko-Labyntseva, Inna V.; Navolokina, Alla S. (LLC "Consulting Publishing Company "Business Perspectives", 2020)
Stakeholder theory dominates in revealing the features of the stakeholders’ influence on various entities; however, only few studies rely on it in the field of enterprises that select banks as financial partners. Considering the enterprise-bank relationship from the stakeholder theory perspective, this paper represents an approach to selecting strategies for interaction with this stakeholder type. The proposed approach includes the following steps: determining the interaction objectives for enterprises and banks; specifying and comparing potential partners; ranking banks to justify the chosen partner/partners for interaction; and selecting interaction strategies and forming the content of the behavior patterns inherent in enterprises (offensive or negotiation strategies). The criteria for choosing a strategy include the objectives of the interaction between enterprises (providing comprehensive services or satisfying individual financial needs) and their financial status that determines the interest of banks in partnership. The application of the proposed methodology for calculating rating indicators and the respective bank ranking showed that 18% of the banks included in the studied list of reliable Ukrainian banks have a high level of innovation activity and an acceptable level of banking service costs for business customers (that is, they implement a customer oriented policy). Therefore, to receive comprehensive banking services combined with high or medium levels of banks’ interest in interaction, the paper recommends enterprises to choose a large-scale offensive strategy or a large-scale negotiation strategy, respectively. The stakeholder theory, as well as consideration of the criteria defined in the paper, will allow enterprises to choose interaction strategies that meet their needs for financial services and harmonize the interests of partners.
Keywords: enterprises; stakeholders; interaction strategies; partnership objectives; bank comparison